The Impact of Artificial Intelligence (AI) on Marketing Strategy - Supriadi, Asep (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research explores the impact of artificial intelligence (AI) on marketing strategy with a focus on contextual understanding of consumers, increasing operational efficiency, better personalization of content, decision-making effectiveness, and the need for integration with expertise. Through systematic literature analysis, this research identifies the positive potential and challenges faced by companies in adopting AI technology in their marketing strategies. The results provide deep insight into how the integration of artificial intelligence can shape modern marketing and deliver significant benefits.